Identification of seedling resistance to stem rust in advanced wheat lines and varieties from Pakistan. Issue 2 (18th March 2020) - Rehman, Monsif Ur; Gale, Sam; Brown‐Guedira, Gina; Jin, Yue; Marshall, David; Whitcher, Lynda; Williamson, Sharon; Rouse, Matthew; Ahmad, Javed; Ahmad, Gulzar; Shah, Irfan Ahmad; Sial, Mahboob Ali; et al.
Abstract: Stem rust is a major disease of wheat ( Triticum aestivum L.) worldwide and new Puccinia graminis f. sp. tritici ( Pgt ) races including TTKSK (Ug99) pose a serious threat to wheat production. The protection of new varieties against Pgt races can be increased by identifying and combining several types of stem rust resistance genes ( Sr ). We screened a set of 707 wheat lines and cultivars against 11 Pgt races under glass house conditions. Of the tested lines, groups of 99, 513, 289, and 515 exhibited low infection type (IT < 3) to races TTKSK, TRTTF, TTTTF, and RRTTF, respectively. Screening against Pgt races (QFCSC, QTHJC, MCCFC, RCRSC, RKRQC, TPMKC, and QCCSM) showed that most of the tested lines were resistant. These lines were screened with eight DNA markers for the presence of Sr2, Sr9a, Sr24, Sr25, Sr31, Sr36, Sr38, and Sr57 genes. Sr36 was absent from all the tested lines, whereas Sr9a was detected in four lines. The marker Sr2_ger93p predicted the presence of Sr2 in 40 lines, and marker barc71 suggested the presence of Sr24 in 12 lines. Sr25 and Sr38 were present in 13 and 54 lines, respectively. The highest frequency of Sr genes was observed for Sr57 (199 lines) and Sr31 (177 lines). Except for lines carrying Sr25 and/or Sr24 genes, most lines were susceptible to Pgt race TTKSK. Since Ug99 is overcoming Sr genes worldwide, including Sr24 and Sr36, a strategy to pyramid multiple Sr genes in new cultivars should be pursued to achieve a durable control of stem rust. The effectiveness of lines such as NRL0902, 11050, B‐2(RF)‐11, and CCRI‐6, found in the current study and featuring other Sr genes, warrants further investigation to identify the source of their resistance and use it in Pakistan wheat breeding programs.